EP1346 Paraaortic lymphadenectomy: step by step surgical education video. (1st November 2019) - Selcuk, I; Oz, M; Toyran, A; Tatar, I; Engin-Ustun, Y; Demiryurek, D
Abstract : Introduction/Background: Paraaortic lymphadenectomy is a part of surgical staging in gynecologic oncology practice. Methodology: This cadaveric educational video shows the technique of paraaortic lymph node dissection in a step by step manner. Results: Boundaries of paraaortic lymphadenectomy; right-right psoas major muscle, ascending colon, right ureter; left-mesentery of descending colon and sigmoid colon, inferior mesenteric vein; caudal-mid common iliac level, below the aortic bifurcation; cranial-left renal vein; posterior-anterior longitudinal ligament. Small intestines are packed cranio-laterally and mesentery of sigmoid colon is retracted caudo-laterally. Posterior parietal peritoneum is cut from the level of ileocolic junction to the level of ligament of Treitz. Paracaval space is developed; right ovarian vessels and right ureter is identified. Horizontal part of duodenum is mobilized and retracted superiorly. Left renal vein is identified. The areolar tissue between the left common iliac artery and mesentery of sigmoid colon is opened, by the way the left ureter and inferior mesenteric artery is identified. The paraaortic lymph node dissection begins over the right common iliac artery from the mid-level caudad to cephalad direction. Precaval and preaortic lymph nodes are dissected to the level of left renal vein. Lateral aortic lymph nodes are dissected from the infra-mesenteric region (low paraaortic), below the level of inferior mesenteric artery. Lateral aortic lymph nodes superior to the level of inferior mesenteric artery (high paraaortic) are identified by sharp and blunt dissection from the mesentery of descending and sigmoid colon and underlying left Gerota's fascia. Lateral aortic lymph nodes are dissected from the supra-mesenteric region, between the inferior mesenteric artery and left renal vein. Conclusion: Aortic bifurcation, common iliac artery, common iliac vein, abdominal ureter, inferior mesenteric artery, ovarian artery, ovarian vein, left renal vein, lumbar vein, lumbar artery, inferior vena cava and aorta are the basic anatomic landmarks for a proper paraaortic lymphadenectomy. Disclosure: Nothing to disclose